Sapote Fruit Fly, Serpentine Fruit Fly, Anastrepha serpentina (Wiedemann) (Insecta: Dipera: Tephritidae) - Howard V. Weems, Jr. (EDIS, 2004)
The sapote fruit fly, Anastrepha serpentina (Wiedemann), sometimes called the serpentine fruit fly, is intercepted frequently in United States ports of entry in various hosts from several countries. It is an important species in Mexico because its larvae infest sapote (Caloca.rpum spp.), sapodilla (Achras zapota), willowleaf lucuma (Lucuma salicifolia) and related fruits. This document is EENY-206 (originally published as DPI Entomology Circular 91), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2001.